PENERAPAN KONSEP CHARACTER, CAPACITY, CAPITAL, COLLATERAL, CONDITION (5C) DALAM SISTEM PEMBERIAN KREDIT USAHA MIKRO PADA PT BANK MANDIRI (PERSERO) TBK UNIT MANDIRI MITRA USAHA BALIKPAPAN UNIVERSITAS BALIKPAPAN - Linda Wulan Sari; Casmudi Casmudi; Sugianto Sugianto (Jurnal Edueco, 2018)
ABSTRACT The focus of the problem is on the application of the Character, Capacity, Capital, Collateral, Condition (5C) Concepts in the Micro Business Credit System, particularly Bank Mandiri, which includes how to apply the 5C principle itself, obstacles that arise when implementation occurs, and also how to overcome these obstacles. The cornerstone of theory uses (Muchtar, Rahmidani, Siwi, 2016) Jakarta Kencana, Banks and Other Financial Institutions. Openness between customers to banks is one of the basis for providing healthy credit. The purpose of this study is to find out how the process of taking credit at Bank Mandiri is carried out, whether it is in accordance with the Standard Operation Procedure procedure or there is a provision for the unit to be the subject of approval. The object of this research is the credit processor or in this case the bank and the customer. Data collection techniques are carried out by interviews, observation and documentation. Data analysis techniques are carried out by source triangulation. The results of the study conclude that: (1) the application of the 5C principle has an effect on the lending process at PT Bank Mandiri (Persero) tbk. (2) barriers experienced include lack of openness between customers and banks, poor credit history, submission of unreasonable credit scores, less productive businesses, lack of additional guarantees, and dubious business legality (3) ways to overcome credit failed that is by giving SP1, SP2. Then SP3 until the execution of the guarantee but can also be done in other ways such as still trying to get closer and maintain good relations with customers.